2018
DOI: 10.1111/sms.13270
|View full text |Cite
|
Sign up to set email alerts
|

Does normalization of voluntary EMG amplitude to MMAX account for the influence of electrode location and adiposity?

Abstract: Voluntary surface electromyography (sEMG) amplitude is known to be influenced by both electrode position and subcutaneous adipose tissue thickness, and these factors likely compromise both between- and within-individual comparisons. Normalization of voluntary sEMG amplitude to evoked maximum M-wave parameters (M peak-to-peak [P-P] and Area) may remove the influence of electrode position and subcutaneous tissue thickness. The purpose of this study was to: (a) assess the influence of electrode position on volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Data in this experiment indicated that peak muscle activation recorded with surface EMG exhibited no relationship with PPO and thus was not a meaningful determinant of PPO in elite cyclists. Therefore, it is possible that more accurate and sensitive measures of neuromuscular activation, perhaps including surface EMG from more muscles and multiple sites per muscle, as well as alternative normalization techniques, might reveal a greater role for activation in determining PPO. However, given that muscle morphology explained 87% of the variability in PPO, the unexplained variance was relatively small (13%) and the contribution of other independent factors, including neuromuscular activation, appears limited for this performance task.…”
Section: Discussionmentioning
confidence: 99%
“…Data in this experiment indicated that peak muscle activation recorded with surface EMG exhibited no relationship with PPO and thus was not a meaningful determinant of PPO in elite cyclists. Therefore, it is possible that more accurate and sensitive measures of neuromuscular activation, perhaps including surface EMG from more muscles and multiple sites per muscle, as well as alternative normalization techniques, might reveal a greater role for activation in determining PPO. However, given that muscle morphology explained 87% of the variability in PPO, the unexplained variance was relatively small (13%) and the contribution of other independent factors, including neuromuscular activation, appears limited for this performance task.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle size was included as an additional index of training status and morphological differences between the three groups. MED was measured to allow for the correction of the pronounced, confounding influence of subcutaneous tissue thickness, primarily body fat, on voluntary EMG amplitude…”
Section: Methodsmentioning
confidence: 99%
“…Correcting EMG amplitude measurements for the amount of subcutaneous tissue at the recording site or using MED as a covariate within statistical testing are approaches that have previously been employed. The MED correction in the current study involved summating the individual's residual absolute agonist EMG amplitude, in comparison to the cohort relationship with MED (eg, agonist EMG amplitude vs MED), with the pooled group mean for absolute agonist EMG amplitude . Overall corrected agonist EMG during all maximum and sub‐maximum contractions was then calculated by averaging the corrected EMG amplitude measurements from each EMG recording site.…”
Section: Methodsmentioning
confidence: 99%
“…Torque and root-mean-square background EMG activity (RMS EMG) were assessed in the 100ms epoch preceding the stimulus. RMS EMG of TA was normalised to Mmax (RMS/Mmax) in order to remove the confounding effect of electrode location and body fat (65), and account for changes at the skin-electrode interface and differences in propagation along the sarcolemma (83). Torque variability during submaximal contractions was assessed as coefficient of variation (CVtorque = SD torque /mean torque*100) in the 1-second epoch preceding the stimulus.…”
Section: Discussionmentioning
confidence: 99%